PENERAPAN MODEL UP WIND, EKSPONENSIAL, DAN CENTRAL DIFFERENCE PADA METODA ANALISA SUB BULUH - Nathanael P Tandian; Aryadi Suwono; Winarto Winarto (Mesin, 2003)
Sub-channel analysis is a method for analyzing thermal hydraulic aspects of nuclear reactors or heat exchangers. The analysis calculates distributions of fluid temperature, pressure, axial velocity, transverse velocity, and fuel rod temperature or heat flux. This paper deals with efforts for improving the accuracy of the sub-channel method. Three numerical schemes for evaluating transversal advective heat rates, i.e.: up wind, exponential, and central difference schemes, were compared. The differences among calculation results obtained by programs that apply these schemes were insignificant. The paper also seeks the best definition of averaged temperature for evaluating physical properties of control volume. It was found that accuracy of the sub-channel method can be improved if the volume-averaged and area-averaged enthalpy in the energy equation, and the volume-averaged density in the axial momentum equation were evaluated based on the fluid temperatures at the middle of control volumes.